CAPILLARY ELECTROPHORESIS AS A VERIFICATION TOOL FOR IMMUNOCHEMICAL DRUG SCREENING - Znaleziona, Joanna; Petr, Jan; Maier, Vitezslav; Knob, Radim; Horakova, Jana; Smetanova, Dana; Sevcik, Juraj (Biomedical papers, 2007)
Background: The aim of this work was to develop a simple capillary electrophoretic method as the verification and confirmation tool in the screening analysis for amphetamines, opiates, benzodiazepines and cocaine and their metabolites for toxicological applications.Methods: 50 mM phosphate Tris pH 2.0 with 30 % (v/v) of methanol was used as a background electrolyte that enabled fast separation of drugs and their metabolites in saliva and urine. Verification of the data from the electrophoretic method was done by High Performance Thin Layer Chromatography (HPTLC) and the immunochemical screening test QuikScreen.Results: The experimental conditions of the Capillary Electrophoresis (CE) were partially optimized (mainly the infl uence of concentration and types of additives, e.g. cyclodextrines, organic solvents) and validated; the method was used for analysing samples from drug abusers.Conclusions: The non-instrumental, immunoassay tests could only confirm qualitative addictions and are mainly employed when the emergency detection of drugs is needed. For quantitative analysis and verification of obtained results the confirmation step is strongly recommended. The simple screening capillary zone electrophoresis method allows recognition of the most abused drugs. The agreement of the results from CE, HPTLC and QuikScreen test was more than 95 %.
Keywords: Capillary electrophoresis/Drug abuse/Toxicological screening/Immunochemical analysis/Clinical toxicology